Fieldwork Experiences in Criminology and Security Studies: Methods, Ethics, and Emotions - Díaz Fernández, Antonio M.; Del-Real, Cristina; Molnar, Lorena (Springer International Publishing, 2023)
Foreword -- Introduction -- Chapter 1. Talking with spies: from naïve to distrustful researcher -- Chapter 2. Doing research on, for and with Police in Canada and Switzerland: Practical and methodological insights -- Chapter 3. Research in probation settings: experience and “field policy” -- Chapter 4. Silence of the altars: Researching sexual abuse in religious institutions in Catalonia (Spain) -- Chapter 5. Studying the military: unlocking a closed organization -- Chapter 6. Researching the elites of power: the case of the parliamentarians -- Chapter 7. Challenges and complexities when researching vulnerable populations and sensitive topics: Working with women experiencing violence and homelessness -- Chapter 8. Researching party zones: Drugs, alcohol, and the night -- Chapter 9. Conducting criminological practitioner research with sex workers in Switzerland -- Chapter 10. Fieldwork and ethical challenges on criminological research with immigrants -- Chapter 11. Researching the Roma in criminology and legal studies: Experiences from urban and rural participant observation, interviews and surveys -- Chapter 12. Street children, criminological research and emotional labour: Reflections from the field -- Chapter 13. Research in child and adolescent victimization: Incentives, threats and challenges -- Chapter 14. Research with trafficking victims. Exploring methods, ethics and emotions -- Chapter 15. How to do criminological research on, for, and with children and young people -- Chapter 16. Researching imprisoned persons: Views from Spain and Latin America -- Chapter 17. Language, emotions, and access to refugee women: Ingredients for reflexivity -- Chapter 18. Gangs: Fieldwork experiences, ethical dilemmas, and emotions in youth street groups research -- Chapter 19. Exploring organized crime beyond institutional sources -- Chapter 20. How to investigate a criminal psychopath? -- Chapter 21. Researching extremists and terrorists: Reflections on interviewing hard-to-reach populations -- Chapter 22. Conducting research with, and on perpetrators of domestic and family violence: insights from Australian research -- Chapter 23. Protecting them, protecting you: tips and cautions when doing research in sexual offending -- Chapter 24. Control, confusion, and failure: Fieldwork in areas of violent conflict and limited state authority -- Chapter 25. Using ethnography to access, understand and reflect on video observation of violence -- Chapter 26. Researching cybersecurity governance: Insights from fieldwork with cybersecurity experts and end-users -- Chapter 27. Fieldwork experiences researching cybercriminals -- Chapter 28. Hidden platforms for cybercrime: Experiences investigating darknet service -- Chapter 29. Conducting psychosocial research with victims of sexting and online sexual victimization -- Chapter 30. Researching cyberbullying: A colorful palette of methods and experiences -- Chapter 31. Researching hate: Negotiating the digital as field site in the study of extremist cultures and propaganda online -- Chapter 32 Deciphering the unspoken: A collective examination of sensitive fieldwork experiences in Criminology and Security Studies.